Alpha-1-antitrypsin: a novel predictor for long-term recovery of chronic disorder of consciousness. (4th March 2018) - Bao, Wangxiao; He, Fangping; Gao, Jian; Meng, Fanxia; Zou, Hai; Luo, Benyan
ABSTRACT: Background : The aim of this manuscript was to explore the molecular basis and identify novel biomarkers for the diagnosis and prognosis of patients with chronic disorder of consciousness. Methods : A coupled isobaric tag for relative and absolute quantitation-based approach was used to screen differentially expressed proteins (DEPs) between patients with chronic disorder of consciousness and healthy individuals. Candidate proteins were identified and measured. The Coma Recovery Scale-Revised (CRS-R) score was used to quantify the severity, and long-term recovery was assessed by Glasgow Outcome Scale (GOS). Results : Between patients and controls, a total of 77 DEPs were identified. Based on the DEPs, a network containing 50 nodes and 207 edges was built, and alpha-1-antitrypsin was marked as the hub protein. The results indicated that alpha-1-antitrypsin correlated with the CRS-R score with a correlation coefficient of 0.631, and an outcome at 12 months (8.5 ± 2.1 ng/ml in patients with GOS 1–2 vs. 6.8 ± 1.6 ng/ml in those with GOS 3–5, p  = 0.002). Conclusions : The data confirm the diagnostic and prognostic potential of alpha-1-antitrypsin in chronic disorder of consciousness, which may contribute to the development of novel therapeutic agents.